2012
DOI: 10.1556/jba.1.2012.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain activity in response to problem solving during the abstinence from online game play

Abstract: Background and aims:Several studies have suggested that addictive disorders including substance abuse and pathologic gambling might be associated with dysfunction on working memory and prefrontal activity. We hypothesized that excessive online game playing is associated with deficits in prefrontal cortex function and that recovery from excessive online game playing might improve prefrontal cortical activation in response to working memory stimulation. Methods: Thirteen adolescents with excessive online game pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Furthermore, the greater activity in the PMC-cerebellar loop was demonstrated in substance dependence [63], implicating the overactivation of habitual process. Analogous results were also observed in IA [64]. In our study, the increased rsFC between the PMC and cerebellum was observed, which further illustrated the possible mechanisms underlying the compulsive use of Internet in IA individuals.…”
Section: 2supporting
confidence: 88%
“…Furthermore, the greater activity in the PMC-cerebellar loop was demonstrated in substance dependence [63], implicating the overactivation of habitual process. Analogous results were also observed in IA [64]. In our study, the increased rsFC between the PMC and cerebellum was observed, which further illustrated the possible mechanisms underlying the compulsive use of Internet in IA individuals.…”
Section: 2supporting
confidence: 88%
“…; Kim et al . 2012a,b), and the mean age of IGD subjects was 21.2 years. The mean time spent on‐line by IGD individuals was 36.4 hours/week.…”
Section: Resultsmentioning
confidence: 99%
“…Because we noted that hyperactivity in the left precentral gyrus (Talairach coordinates: −50,−6, 34, voxel number = 88; Z = 2.274; P = 0.000) was reported in only three studies, therefore we conservatively do not consider it as a significant finding (Kim et al . ; Dong et al . 2013a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies suggest that cue-induced gaming urge activates the same brain regions (i.e., dorsolateral prefrontal cortex, orbitofrontal cortex, parahippocampal gyrus, and thalamus) that are activated by gambling in the case of pathological gamblers and substance use in the case of substance use abusers (Han et al, 2011;Ko et al, 2009). Other results suggest that the effects of excessive online game playing on working memory may be similar to those observed in patients with substance dependence (Kim et al, 2012). Consequently, researchers assume that problematic online gaming might share the same neurobiological mechanism as pathological gambling and substance dependence (Kuss & Griffiths, 2012c).…”
Section: Neurobiological Aspectsmentioning
confidence: 95%